Relationship between Sleep Quality and Gastritis Symptoms in Students - Irfan Wabula; Masyita Haerianti; Boby Nurmagandi; Evidamayanti Evidamayanti; Anasari Anasari (Indonesian Journal of Global Health Research, 2025)
Gastritis or often called stomach disease is one of the health problems with high prevalence. Gastritis occurs more often in productive age. Students are a productive age group who are busy with various activities. Sleep quality can be one of the factors that can worsen gastritis and even cause death. Objective to determine the relationship between sleep quality and gastritis symptoms in Nursing students of the Faculty of Health Sciences, University of West Sulawesi. Method: This type of research is observational analytic and the sampling technique used in this study is stratified random sampling. The research design used is Cross Sectional. The number of samples is 222 nursing students. Demographic data collection through questionnaires. The statistical test used is the Chi-Square test. There is a relationship between sleep quality and gastritis symptoms in nursing students of the Faculty of Health Sciences, University of West Sulawesi with a p value of 0.037 (p <0.05). There is a relationship between sleep quality and gastritis symptoms in nursing students of the Faculty of Health Sciences, University of West Sulawesi.